Síntese e Caracterização de Membrana de Quitosana com Extrato de Banana Verde e Andiroba para Cicatrização de Lesões Epiteliais - FERREIRA, Elisângela da Silva (Universidade Federal do Pará, 2022)
Biomaterials must enable the surrounging healthy cells to grow and replace the matrix that constitutes the material. The application of other bioactives is being widely studied, as well as the incorporation of phytosan into chemical removal films in wound healing by different techniques. This study aimed to synthesize and characterize chitosan membranes, green banana peel extract and andiroba oil for application in epithelial devices. Membranes were made in different compositions and characterization tests were carried out on the synthesizer. Andiroba oil was added in pure form or oil-in-water (O/W) emulsion in the chitosan solution. Higher in chitosan membranes with emulsion O/W, being 978.79 % e 423.64 %, in Nano M6 and Nano M11, respectively, after 24 hours of life in water. The highest percentage of moisture was in M7 (24.9 ± 3.8 %) and the lowest in Nano M7 (13.46 ± 0.8 %). All samples are hydrophilic, with lower values with banana peel extracts from the first decoction, M1 (24.0° ± 1.9°) and Nano M6 (23.7° ± 4.3°). Diffractograms are mostly amorphous material, for the most part. Thermal analysis has greater stability of chitosan membranes synthesized with banana peel extract and addition of andiroba oil. Spectroscopy showed characteristic peaks and bands of sample components and interaction between these components, as well as suggestion or encapsulation of the oil. The material first presented characteristics of absorption of liquids and synthesized, in particular the membranes of banana extraction of the day of decoction interaction and with addition of O/W emulsions, with greater possibility of duration of its healing of composting epithelial deficiencies.